Cinematie Treatments of Fantasy in Mythology films (Al-Academy, 2024)
Fantasy represents the basic material for science، literature، and all the arts. It is an absolute necessity for building any cinematic genre. It also represents an essential building block that cannot be abandoned in a movie based on a legend. This prompted the researcher to title his research (Cinematic Treatments of Imagination in Legendary Movies. The research consists of four chapters. The first chapter represented the methodological framework and included the research problem، which was represented by the following question: What are the cinematic treatments of imagination in the Legends films? Then the researcher dealt with the importance of the research and its aim، which included revealing the cinematic treatments of imagination in the Legends films، and then the limits of the research. As for the second chapter (theoretical framework and previous studies)، it included two topics: imagination، myths، and exchanges of presence. The third chapter (research procedures) included the research platform، which is the descriptive analytical approach، and the research sample، while the fourth chapter was about the results، conclusions، recommendations، and proposals، and the research concluded with references